Understanding depression - Ainsworth, Patricia, M.D (Understanding health and sickness series., 2000)
"Understanding Depression explores the reality of the illness from the authors twin perspectives as a psychiatrist and as a family member who experienced the tragedy of depression firsthand. Using examples from her practice, she discusses the different type of depression, the kinds of people at risk, and the risk factors of suicide. Using understandable terms, she looks at the way the brain works, how the body communicates with it, and how in depression, as recent discoveries have shown, the process fails." "But understanding depression is only half the battle. Taking personal responsibility for fighting the beast is equally important. Treatment methods, discussed here, include various forms of psychotherapy, different classes of antidepressant medications, and the controversial subjects of "shock" treatment and involuntary treatment."--Jacket